Does administering iodine in radiological procedures increase patient doses?. Issue 11 (30th October 2014) - He, Wenjun; Huda, Walter; Mah, Eugene; Yao, Hai
Abstract : Purpose: The authors investigated the changes in the pattern of energy deposition in tissue equivalent phantoms following the introduction of iodinated contrast media. Methods: The phantom consisted of a small "contrast sphere, " filled with water or iodinated contrast, located at the center of a 28 cm diameter water sphere. Monte Carlo simulations were performed usingmcnp5 codes, validated by simulating irradiations with analytical solutions. Monoenergetic x‐rays ranging from 35 to 150 keV were used to simulate exposures to spheres containing contrast agent with iodine concentrations ranging from 1 to 100 mg/ml. Relative values of energy imparted to the contrast sphere, as well as to the whole phantom, were calculated. Changes in patterns of energy deposition around the contrast sphere were also investigated. Results: Small contrast spheres can increase local absorbed dose by a factor of 13, but the corresponding increase in total energy absorbed was negligible (<1%). The highest localized dose increases were found to occur at incident photon energies of about 60 keV. For a concentration of about 10 mg/ml, typical of clinical practice, localized absorbed doses were generally increased by about a factor of two. At this concentration of 10 mg/ml, the maximum increase in total energy deposition in the phantom was only 6%. These simulations demonstrated that increases in contrast sphere doses were offset by corresponding dose reductions at distal and posterior locations. Conclusions: Adding iodine can result in values of localized absorbed dose increasing by more than an order of magnitude, but the total energy deposition is generally very modest (i.e., <10%). Their data show that adding iodine primarily changes the pattern of energy deposition in the irradiated region, rather than increasing patient doses per se.